MENELADAN FALSAFAH MASYARAKAT BALI DALAM MELAKSANAKAN KEWAJIBAN PAJAKNYA - Kuncoro Aji, Anggit (JURNAL PAJAK INDONESIA, 2024)
This study aims to determine the level of compliance of Balinese people, various Balinese philosophies that play a role in tax compliance, and find out the philosophies that play a role in the green economy. The uniqueness of the religion embraced by the Balinese, namely Hinduism, certainly makes many new philosophies that can be exemplified. The research was conducted with a literature study and the data collection technique was documentation. Data were obtained from various reliable sources then analyzed and conclusions were drawn. The tax compliance indicator used is the level of local tax ratio, which is the ratio between local tax realization and GRDP. This research has several conclusions. First, Balinese people are obedient in paying taxes. Second, the philosophy of Tri Hita Karana, Yadnya, Tri Kaya Parisudha affects the tax compliance of Balinese people. Third, with the implementation of Tri Hita Karana, the Balinese have implemented a green economy. The central tax authority or other regions in Indonesia can make the three Balinese philosophies as educational materials for tax awareness.